Acne in medical students and their associated factors - Flores-Rojas, Cesar (2020)
Introduction: Acne is a chronic inflammatory disease of the multifactorial pilosebaceous unit present in the face, back and chest. In this study we wanted to know what was the frequency and the factors associated with the presence of acne in medical students. Materials and Methods: A case-control study was carried out in students from 1st to 5th year in School of Medicine of the Universidad Nacional Hermilio Valdizán. A 95% CI with an alpha of 0.05 and a power of 80% with a beta equal to 0.20 were considered. Results: The mean age was 22.31 + 3.22 years. Fruit consumption obtained significance (p = 0.04; OR = 6.09) as a protective factor. Anxiety was not significant (p = 0.59; OR = 1.34), as well as nutritional status (p = 0.57; OR = 1.14) and consumption of vitamin B supplement (p = 0.35 ; OR = 0.56). Significance was found in biological inheritance (p = 0.01; OR = 3.74 with lower range = 10.61 and higher range = 1.31). Conclusions: Frequent consumption of fruits proved to act as a protective factor in the development of acne; In addition, it is also concluded that biological inheritance plays an important role in it.